Critical role of the Ror‐family of receptor tyrosine kinases in invasion and proliferation of malignant pleural mesothelioma cells. (29th May 2018) - Saji, Takeshi; Nishita, Michiru; Ogawa, Hiroyuki; Doi, Takefumi; Sakai, Yasuhiro; Maniwa, Yoshimasa; Minami, Yasuhiro
Abstract: Malignant pleural mesothelioma (MPM) is a highly aggressive tumor with poor prognosis and closely related to exposure to asbestos. MPM is a heterogeneous tumor with three main histological subtypes, epithelioid, sarcomatoid, and biphasic types, among which sarcomatoid type shows the poorest prognosis. The Ror‐family of receptor tyrosine kinases, Ror1 and Ror2, is expressed in various types of tumor cells at higher levels and affects their aggressiveness. However, it is currently unknown whether they are expressed in and involved in aggressiveness of MPM. Here, we show that Ror1 and Ror2 are expressed in clinical specimens and cell lines of MPM with different histological features. Studies using MPM cell lines indicate that expression of Ror2 is associated tightly with high invasiveness of MPM cells, whereas Ror1 can contribute to their invasion in the absence of Ror2. However, both Ror1 and Ror2 promote proliferation of MPM cells. We also show that promoted invasion and proliferation of MPM cells by Ror signaling can be mediated by the Rho‐family of small GTPases, Rac1, and Cdc42. These findings elucidate the critical role of Ror signaling in promoting invasion and proliferation of MPM cells. Abstract : We show for the first time that Ror1 and Ror2 are expressed in clinical specimens and cell lines of malignant pleural mesothelioma (MPM) with different histological and pathological features and uncover their roles in regulating proliferation and invasion of MPM cells. Our findings shed novel insight into how Ror signaling acts in conferring aggressiveness to MPM cells.